Republic of Poland : 2013 Article IV Consultation. - International Monetary Fund. European Dept. (Washington, D.C. : International Monetary Fund, 2013)
This staff report for the Republic of Poland's 2013 Article IV Consultation highlights economic development and policies. The current account in 2012 was primarily financed by EU transfers and foreign direct investment (FDI), notwithstanding a reduction in net FDI inflows. Moderate outflows from the domestic banking system were more than offset by strong portfolio inflows into the government bond market. The current account deficit and real effective exchange rate are broadly in line with medium-term fundamentals and desirable policies according to the External Balance Assessment models. The largely foreign-owned banking system has remained well-capitalized, profitable, and liquid.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet